Gangrene of the anterior abdominal wall after orthotopic liver transplantation: invasive cutaneous candidiasis. Issue 812 (June 1993) - Rela, M.; Heaton, N. D.; Vougas, V.; Rolando, N.; Wade, J.; Portmann, B.; Williams, R.; Tan, K. C.
Abstract : Fungal infections following liver transplantation are not uncommon and may be life-threatening. Superficial candidal infections of the bronchus, oesophagus and urinary tract are the most common mode of presentation. Invasive cutaneous and subcutaneous candidiasis is, however, very rare. We report two patients with invasive cutaneous and subcutaneous candidiasis after orthotopic liver transplantation.